Cytotoxicity of extracts from fruit plants against leukemic cell lines - Chadarat Ampasavate (2018)
This study examined the antileukemic activity of non edible parts of 13 common Thai tropical fruits. Their ethanolic extracts were tested for cytotoxic effects on U937, K562, HL60, Molt 4 and normal human peripheral blood mononuclear cells (PBMCs). Three of 20 crude plant extracts (kaffir lime leaves, mangosteen peels, and wampee leaves) had strong cytotoxic effects on K562, U937, and Molt4 cells. The IC50 values of kaffir lime leaves on those cells were 26.1, 9.0 and 11.9 μg/ml respectively, whereas those of mangosteen peel were 23.6, 4.5 and 10.1 μg/ml, and those of wampee leaves were 71.9, 13 and 70.4 μg/ml. Furthermore, pomegranate peel extract had a potent cytotoxic effect on HL60 cells (IC50 of 8.0 μg/ml), but was non-toxic to normal PBMCs, indicating that as a potential source of antileukemic agents. © 2010 Academic Journals.